P311, Friend, or Foe of Tissue Fibrosis? - Stradiot, Leslie; Mannaerts, Inge; van Grunsven, Leo A. (Frontiers in Pharmacology, 2018)
P311 was first described by the group of Studler et al. in the developing brain in 1993. In healthy, but mainly in pathological tissues, P311 is implicated in cell migration and proliferation. Furthermore, evidence in models of tissue fibrosis points to the colocalization with and the stimulation of transforming growth factor β1 by P311. This review provides a comprehensive overview on P311 and discusses its potential as an anti-fibrotic target.